Cytokines as Mediators of Pain-Related Process in Breast Cancer - Carolina Panis; Wander Rogério Pavanelli (Mediators of Inflammation)
Pain is a clinical sign of inflammation found in a wide variety of chronic pathologies, including cancer. The occurrence of pain in patients carrying breast tumors is reported and is associated with aspects concerning disease spreading, treatment, and surgical intervention. The persistence of pain in patients submitted to breast surgery is estimated in a range from 21% to 55% and may affect patients before and after surgery. Beyond the physical compression exerted by the metastatic mass expansion and tissue injury found in breast cancer, inflammatory components that are significantly produced by the host-tumor interaction can significantly contribute to the generation of pain. In this context, cytokines have been studied aiming to establish a cause-effect relationship in cancer pain-related syndromes, especially the proinflammatory ones. Few reports have investigated the relationship between pain and cytokines in women carrying advanced breast cancer. In this scenario, the present review analyzes the main cytokines produced in breast cancer and discusses the evidences from literature regarding its role in specific clinical features related with this pathology.